PERANAN PT DALAM PEMBINAAN SIKAP ILMIAH MAHASISWA - Sukmana, Oman (Jurnal Bestari, 1993)
The role of education become more important and urgent to educate people in order to participate in the process of nation building. Because the success of developoing country is not only based on the natural resources, but also it is based on the human resources, yet they still become under developing coutries. in contras, some coutries which have few natural resources can develop themeselves to modern ones because they have qualified human resources. As a result, education os the best way to qualify the human resources.